Análisis del Acuerdo Comercial Multipartes entre Ecuador y la Unión Europea y su repercusión en el sector automotriz nacional. período 2017-2020 - Morales Silva, Marlon Israel (2022)
Ecuador's automotive import sector was affected by the application of a series of tax and non-tax restrictions applied during the time of Correismo, an economy weakened by the drop in oil prices, an Ecuador closed to international trade, losing competitiveness with its neighboring countries Peru and Colombia are some of the problems that were corrected through the application of the Multiparty Trade Agreement with the European Union in force since January 1, 2017, the Ecuadorian export sector of products such as bananas, cocoa, flowers among others are the most benefited from the application of the Multiparty Agreement. On the other hand, the production of national vehicles is one of the sectors affected by the application of the Multiparty Trade Agreement with the European Union, sales for the national vehicle assembly sector are decreasing, as the years go by they are affected by the reduction of tariffs on vehicles imported from Europe that are increasingly increasing their participation in the Ecuadorian automotive market due to the variety of models, competitive prices and technological benefits that European vehicles have. The little investment of the state to solve the needs of the Ecuadorian assembly sector and an industrial sector stagnant in the third industrial revolution are events to consider and direct Ecuador towards a technological integration based on concepts of the fourth industrial revolution.